2017
DOI: 10.1371/journal.pone.0178363
|View full text |Cite
|
Sign up to set email alerts
|

PEG3 control on the mammalian MSL complex

Abstract: Peg3 (paternally expressed gene 3) encodes a DNA-binding protein that functions as a transcriptional repressor. Recent studies revealed that PEG3 binds to Msl1 (male-specific lethal 1) and Msl3, the two main components of the MSL complex. In the current study, we investigated potential roles of Peg3 in controlling its downstream genes through H4K16ac, the histone modification by the MSL complex. According to the results, complete removal of PEG3 resulted in up-regulation of Msl1 and Msl3, and subsequently an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
2
4
0
Order By: Relevance
“…The results presented here demonstrated that PEG3 may directly control the expression of Oxtr , as a DNA-binding protein ( Fig 1 and Fig 2 ). This also agrees with the previous studies that PEG3 functions as a DNA-binding protein controlling the expression of several downstream genes, including Pgm2l1 , H19 , Msl1 and Msl3 [ 4 7 ]. PEG3 has been predicted to be a transcriptional repressor, since the known downstream genes tend to be up-regulated in the mutant samples lacking PEG3 [ 6 , 7 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The results presented here demonstrated that PEG3 may directly control the expression of Oxtr , as a DNA-binding protein ( Fig 1 and Fig 2 ). This also agrees with the previous studies that PEG3 functions as a DNA-binding protein controlling the expression of several downstream genes, including Pgm2l1 , H19 , Msl1 and Msl3 [ 4 7 ]. PEG3 has been predicted to be a transcriptional repressor, since the known downstream genes tend to be up-regulated in the mutant samples lacking PEG3 [ 6 , 7 ].…”
Section: Discussionsupporting
confidence: 93%
“…PEG3 also contains a KRAB-A domain, thus is predicted to be a transcriptional repressor through its interaction with KAP1 [ 8 ]. This predicted repression function has been further confirmed through the observation that the expression levels of its downstream genes are usually up-regulated in the tissues of the mouse mutant models targeting Peg3 [ 6 , 7 ]. According to the results from mouse knockout (KO) models, Peg3 is also involved in controlling fetal growth rates and maternal-caring behaviors [ 9 13 ].…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…The Peg3 dosages also affected the expression levels of Acly in embryos (Figs 3 , 4A and 4B ). These results comply with the previous studies showing the DNA-binding capability of PEG3 and controlling the expression levels of several downstream genes, including Oxtr , H19 , Msl1 , and Msl3 [ 34 , 44 , 46 , 47 ]. In the mammary gland, Peg3 dosage appeared to be associated with the expression level of the key gene, Acly , connecting the glucose metabolism and lipid synthesis ( Fig 6 ).…”
Section: Discussionsupporting
confidence: 93%
“…To estimate the enrichment of H3K4me3, H3K36me3, RNA PolII S5P, and H4K16ac in our gene categories, we retrieved the available ChIP-seq datasets for MEF cells from GSE33823 [33] , GSE36905 [34] for H3K4me3, H3K36me3, RNAPolII S5P and GSE97459 [35] for H4K16ac. [41,42].…”
Section: Chip-seq Analysismentioning
confidence: 99%